COMENTARIOS AL CODIGO DE DERECHO CANONICO - Cabreros de Anta, Marcelino (autor) (BIBLIOTECA DE AUTORES CRISTIANOS, NORMAL;, 1963)
CONTENIDO: V.1 CANONES 1-681.-- V.2 CANONES 682-1321.-- V.3 CANONES 1322-1998.-- V.4 CANONES 1999-2414